Predictors of skin cancer in commercial airline pilots - Nicholas, Joyce S. (Oxford University Press, 2009)
Background Skin cancers among commercial airline pilots have been reported to occur at increased rates in pilot populations worldwide. The reasons for these increases are unclear, but postulated factors include ionizing radiation, circadian disruption and leisure sun exposure. Aims To investigate the potential association of these occupational and lifestyle factors, as well as medical history and skin type, with non-melanoma skin cancer in pilots. Methods Data were collected using a confidential Internet survey administered in collaboration with the Air Line Pilots Association International to all active pilots in four US commercial airlines. Pilots with non-melanoma skin cancer were compared to those without using multivariable analysis. Results The response rate was 19%. Among pilots flying <20 years prior to diagnosis, factors associated with increased odds of non-melanoma skin cancer were at-risk skin type, childhood sunburns and family history of non-melanoma skin cancer. Off-duty sunscreen use and family history of melanoma were protective. Among pilots with ≥20 years flight time prior to diagnosis, childhood sunburns and family history of non-melanoma skin cancer persisted as risk factors, with the addition of flight time at high latitude. Conclusions Further investigation regarding the potential health impact of long-term flying at high latitudes is recommended. Additionally, occupational health programmes for pilots should stress awareness of and protection against established risk factors for non-melanoma skin cancer.